Sinners of Starlight City : a novel [large type] - Scott, Anika (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
"From the author of the international bestseller The German Heiress, a gripping historical drama about a woman determined to avenge the crimes against her family, set at the 1933 Chicago World's Fair. "The magnificent Anika Scott has written a lush and beautifully rendered novel that will keep you turning pages long into the night."--Adriana Trigiani, New York Times bestselling author of The Good Left Undone. Vengeance is in the family, and the family is a bond like no other. It's the worst year of the Great Depression, and America needs all the hope it can get. The Chicago World's Fair, a glittery city-within-a-city, becomes a symbol of the good that's yet to come. But every utopia has a seedy side--and that's Rosa Mancuso's world. As the mysterious Madame Mystique she mixes magic with a dose of bare skin burlesque, bringing customers to the home of the Fair's carnival rides and spectacles. Rosa doesn't perform for fame, though. She has come from Mussolini's Italy to America, where she's plotting her revenge for the murders of her family. The perpetrator will soon arrive at the World's Fair via a celebrated Italian air fleet, and Rosa is determined to be prepared. But when her estranged cousin, Mina, comes to her desperate for help, with a dangerous mobster close on her heels, Rosa agrees to protect Mina and her new baby, born across the color line. With the clock ticking, Rosa decides the only way to survive is to make vengeance a family affair and prompt everyone to, at last, confront the sins from their pasts. A gripping story of retribution, belonging, and survival, Sinners of Starlight City boldly explores the complexity of identities straddling ethnic lines and asks, who gets to decide who we are and where we belong?" -- ONIX annotation